Evolução temporal do tabagismo em estudantes de medicina, 1986, 1991, 1996 Trends in smoking habits among medical students in 1986, 1991, 1996 - Ana Menezes; Eduardo Palma; Ricardo Holthausen; Ricardo Oliveira; Pablo S Oliveira; Eduardo Devens; Luciane Steinhaus; Bernardo Horta; Cesar G Victora (Universidade de São Paulo, 2001)
OBJETIVO: Avaliar a tendência temporal do tabagismo em estudantes de medicina nos últimos dez anos. MÉTODOS: Realizou-se estudo transversal com estudantes do primeiro ao quinto ano do curso de medicina, em 1996. A amostra foi de 449 alunos que responderam a questionário auto-aplicável. Fumante era aquele que fumava um ou mais cigarros por dia há pelo menos um mês; ex-fumantes foram aqueles que, no período da entrevista, não eram fumantes regulares, mas o haviam sido anteriormente. Pesquisa similar foi realizada em 1986 e 1991. RESULTADOS/CONCLUSÕES: A prevalência de tabagismo foi de 11%, comparada com 14% em 1991 e 21% em 1986. Apesar da redução do tabagismo nas três séries estudadas, a queda percentual entre 1996 e 1991 foi menor do que aquela observada entre 1991 e 1986. Em 1996, a prevalência do vício de fumar aumentou conforme o ano cursado. Não houve diferenças significativas quanto ao sexo. A maioria dos alunos mostrou-se favorável à proibição do fumo em locais de ensino e assistência e afirmaram que o tema era pouco valorizado no currículo da faculdade. OBJECTIVE: To evaluate trends in smoking habits among medical students in the last ten years. METHODS: In 1996, a cross-sectional survey of smoking habits was carried out among students in the first to the fifth year of medical school. Four hundred and nine students answered the questionnaire. A regular smoker was defined as someone who smokes one or more cigarettes a day at least for one month; former smokers were the ones who used to smoke in the past but not at the moment. Similar researchs were conducted in 1986 and 1991. RESULTS/CONCLUSIONS: Smoking prevalence was 11% compared with 14% in 1991 and 21% in 1986. Although there was a significant reduction of smoking in the last three years, the actual decrease from 1991 to 1996 was less than that observed from 1986 to 1991. In 1961, the prevalence of smoking increased in the last years of medical school. There were no significant differences regarding gender. Most of the students were in favor of not allowing smoking in both the school areas and hospital wards. They also mentioned in their questionnaire that smoking was poorly approached during medical school.